Половці: етнічна історія - Половець, В. (Сiверянський лiтопис, 2016)
У статті розглядається етнічна історія половців у їх часовому і просторовому русі. Простежується утворення племен і союзів племен, їхнє розселення у певних регіонах, співвідношення між соціальними верствами та умовами існування. Основна увага зосереджена на становленні етносів різного таксономічного рівня: вивченні й опису трансформації племен та їхніх союзів, розселенню у межах етнічної території, родовому укладу, історії боротьби за своє існування. В статье рассматривается этническая история половцев в их часовом и пространственном движении. Прослеживается образование племён и союзов племён, их расселение в определённых регионах, соотношение между социальными вёрствами и условиями существования. Основное внимание сосредоточено на становлении этносов разного таксономического уровня: изучении и описании трансформации племён и их союзов, расселении в границах этнической территории, родовому укладу, истории борьбы за своё существование. Thus, research of ethnic history of Polovtsians (according to the Old Russian annals) or Kipchaks (according to the Muslim sources) or Komans, Plavtsians and Palochivs (according to the West European chronicles) or Kynchivs, Syrivs, Hardynivs (according to the Arabic and Persian medieval annals) – all these various ethnic names, which in a strange rarity were given by scientists from different countries to the same people, is important. It seems that marked polyonymous tribes, which only appeared at the beginning of II millennium AC, and became the object of attention of historians, geographers, linguists and travelers. Detailed information about them spread in different languages of the world. The beginning was put by Chinese chronicles, which reported that Seyanto tribes were a nomad the steppes from Altai to The Great Wall of China. Arabic annalists attribute the mention about Kipchak tribes to VII century. Turkic and Uighuric sources, keeping information about Seyanto, at the same time call them «Syries» and «Kipchaks». After the defeat of Uighuric the Seyanto Khanate at the head with Kipchaks, the last were forced to migrate to the steppes of Eastern and Central Kazakhstan, where mingling with tribes of Kyrgyz, Tyurheshiv-Azgishiv and Oguz and left a noticeable track in a material culture of Kazakhstan and peoples of Central Asia. Natives of the Tatar-Mongol ethnos, which included Kipchaks, Kymaks and their companions, were the result of united politically, similar in origin, language and culture of Nomads that at X – early XI century were settled on Kazakh land. Later, as a result of their great migration, the western branch of Kipchaks (Polovtsians) moved to southern Ukrainian steppes, leaving the eastern part of Kipchaks and Kymaks at the large territory of Kazakhstan.